Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(M=a\left(a+b\right)\left(a+c\right)=a\left(a^2+ac+ba+bc\right)\)
\(=a^3+a^2c+a^2b+abc=a^2\left(a+b+c\right)+abc\)
\(=a^20+abc=abc\) (1)
\(N=b\left(b+c\right)\left(b+a\right)=b\left(b^2+ba+cb+ca\right)\)
\(=b^3+b^2a+b^2c+abc=b^2\left(a+b+c\right)+abc\)
\(=b^20+abc=abc\) (2)
\(P=c\left(c+a\right)\left(c+b\right)=c\left(c^2+cb+ac+ab\right)\)
\(=c^3+c^2b+c^2a+abc=c^2\left(a+b+c\right)+abc\)
\(c^20+abc=abc\) (3)
từ (1);(2)và(3) ta có : \(M=N=P=abc\)
vậy khi \(\left(a+b+c\right)=0\)thì \(M=N=P\) (đpcm)
Ta có :a+b+c=0\(\Rightarrow\)\(\left\{{}\begin{matrix}a+b=-c\\a+c=-b\\b+c=-a\end{matrix}\right.\) (1)
Thay (1)vào M:\(\Rightarrow\) M = a(-c)(-b)=abc
Thay (1)vào N:\(\Rightarrow\) N = b(-a)(-c)=abc
Thay (1)vào P:\(\Rightarrow\) p = c(-b)(-a)=abc
\(\Rightarrow\)M=N=P
\(a+b+c=0\)
\(\Rightarrow\)\(\hept{\begin{cases}a+b=-c\\a+c=-b\\b+c=-a\end{cases}}\)
\(M=a\left(a+b\right)\left(a+c\right)=a.\left(-c\right).\left(-b\right)=abc\)
\(N=b\left(b+c\right)\left(a+b\right)=b.\left(-a\right).\left(-c\right)=abc\)
\(P=c\left(b+c\right)\left(a+c\right)=c.\left(-a\right).\left(-b\right)=abc\)
\(\Rightarrow\)\(M=N=P\)
A=(a+b)(b+c)(c+a)+abcA=(a+b)(b+c)(c+a)+abc
=a2b+ab2+a2c+ac2+b2c+bc2+2abc+abc=a2b+ab2+a2c+ac2+b2c+bc2+2abc+abc
=ab(a+b+c)+bc(a+b+c)+ca(a+b+c)=ab(a+b+c)+bc(a+b+c)+ca(a+b+c)
=(a+b+c)(ab+bc+ca)=(a+b+c)(ab+bc+ca)
Vậy....
Do a+b+c = 0
=>\(\hept{\begin{cases}a+b=-c\\a+c=-b\\b+c=-a\end{cases}}\)
=>\(\hept{\begin{cases}M=a\left(-c\right)\left(-b\right)=abc\\E=b\left(-a\right)\left(-c\right)=abc\\H=c\left(-b\right)\left(-a\right)=abc\end{cases}}\)
=> M = E = H